Identifying HSV-1 Inhibitors from Natural Compounds via Virtual Screening Targeting Surface Glycoprotein D - Jiadai Wu; Helen Power; Monica Miranda-Saksena; Peter Valtchev; Aaron Schindeler; Anthony L. Cunningham; Fariba Dehghani (MDPI AG, 2022)
Herpes simplex virus (HSV) infections are a worldwide health problem in need of new effective treatments. Of particular interest is the identification of antiviral agents that act via different mechanisms compared to current drugs, as these could interact synergistically with first-line antiherpetic agents to accelerate the resolution of HSV-1-associated lesions. For this study, we applied a structure-based molecular docking approach targeting the nectin-1 and herpesvirus entry mediator (HVEM) binding interfaces of the viral glycoprotein D (gD). More than 527,000 natural compounds were virtually screened using Autodock Vina and then filtered for favorable ADMET profiles. Eight top hits were evaluated experimentally in African green monkey kidney cell line (VERO) cells, which yielded two compounds with potential antiherpetic activity. One active compound (1-(1-benzofuran-2-yl)-2-[(5Z)-2H,6H,7H,8H-[1,3] dioxolo[4,5-g]isoquinoline-5-ylidene]ethenone) showed weak but significant antiviral activity. Although less potent than antiherpetic agents, such as acyclovir, it acted at the viral inactivation stage in a dose-dependent manner, suggesting a novel mode of action. These results highlight the feasibility of in silico approaches for identifying new antiviral compounds, which may be further optimized by medicinal chemistry approaches.